Biochemical correlate of dimorphism in a zygomycete benjaminiella poitrasii: characterization of purified NAD-dependent glutamate dehydrogenase, a target for antifungal agents - Joshi, C. V.; Pathan, E. K.; Punekar, N. S.; Tupe, S. G.; Kapadnis, B. P.; Deshpande, Mukund V. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2013)
The fungal organisms, especially pathogens, change their vegetative (Y, unicellular yeast and H, hypha) morphology reversibly for survival and proliferation in the host environment. NAD-dependent glutamate dehydrogenase (NAD-GDH, EC 1.4.1.2) from a non-pathogenic dimorphic zygomycete Benjaminiella poitrasii was previously reported to be an important biochemical correlate of the transition process. The enzyme was purified to homogeneity and characterized. It is a 371 kDa native molecular weight protein made up of four identical subunits. Kinetic studies showed that unlike other NAD-GDHs, it may act as an anabolic enzyme and has more affinity towards 2-oxoglutarate than l-glutamate. Chemical modifications revealed the involvement of single histidine and lysine residues in the catalytic activity of the enzyme. The phosphorylation and dephosphorylation study showed that the NAD-GDH is present in active phosphorylated form in hyphal cells of B. poitrasii. Two of the 1,2,3 triazole linked beta-lactam-bile acid conjugates synthesized in the laboratory (B18, B20) were found to be potent inhibitors of purified NAD-GDH which also significantly affected Y-H transition in B. poitrasii. Furthermore, the compound B20 inhibited germ tube formation during Y-H transition in Candida albicans strains and Yarrowia lipolytica. The possible use of NAD-GDH as a target for antifungal agents is discussed.
Keywords: Antifungal agent; Benjaminiella poitrasii; Biochemical correlate of dimorphism; Candida albicans; NAD-GDH activity regulation; Yarrowia lipolytica; Yeast-hypha reversible transition